The Potential of Telemedicine to Improve Pediatric Concussion Care in Rural and Remote Communities in Canada - Ellis, Michael J.; Russell, Kelly (Frontiers in Neurology, 2019)
Concussion is a form of mild traumatic brain injury that affects thousands of Canadian children and adolescents annually. Despite national efforts to harmonize the recognition and management of pediatric concussion in Canada, timely access to primary and specialized care following this injury remains a challenge for many patients especially those who live in rural and remote communities. To address similar challenges facing patients with stroke and other neurological disorders, physicians have begun to leverage advances in telemedicine to improve the delivery of specialized neurological care to those living in medically underserved regions. Preliminary studies suggest that telemedicine may be a safe and cost-effective approach to assist in the medical care of select patients with acute concussion and persistent post-concussion symptoms. Here we provide an overview of telemedicine, teleneurology, the principles of concussion assessment and management, as well as the current state of concussion care in Canada. Utilizing preliminary evidence from studies of telemedicine in concussion and experience from comprehensive systems of care for stroke, we outline steps that must be taken to evaluate the potential of telemedicine-based concussion networks to improve the care of pediatric concussion patients living in underserved rural and remote communities in Canada.